Immunology of lyme borreliosis - Satz, N... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
Borrelia burgdorferi shows both a variety of outer surface proteins with molecular weights between 14 and 100 kilo-Dalton and a 41 kilo-Dalton flagellar protein which induce the immunologic repoonse in the infected host. Lipopolysaccharides are responsible for inflammatory reactions and for constitutonal symptoms. A vigorous T-cell immune response first develops followed by a more slowly evolving B-cell immune response later on. The humoral response shows the usual pattern of IgM antibodies appearing first, followed by IgG and IgA antibodies. The igM antibody titre may normalize after recovery while the IgM titre may persist over years or decades. Antibodies to flagellin or to the 60 and 100 kilo-Dalton surface proteins first appear in the course of the disease, later on antibodies to OspA, OspB and OspC can be found. However, elevated ELISA, immunofluorescence titres or the immunoblot do not confirm the diagnosis of Lyme Borreliosis. The diagnosis has to be made clinically and by excluding other diagnoses.
Keywords: Borrelia burgdorferi; Immunology; Lyme disease; Pathogenicity